Altruism, Fairness and Evolution: the Case for Repeated Stochastic Games - Matthijs van Veelen (Tinbergen Institute, 2002)
This paper is an effort to convince the reader that using a stochastic stage game in a repeated setting - rather than a deterministic one - comes with many advantages. The first is that as a game it is more realistic to assume that payoffs in future games are uncertain. The second is that it allows for strategies that make an evolutionary approach possible, while folk theorem strategies do not allow for such an analysis. But the most important feature is that such a setting allows for equilibrium strategies that look very much like human behaviour; altruism and fairness will be shown to feature in a natural way in equilibrium.
Keywords: C70; 330; Altruismus; Theorie; Wiederholte Spiele; Stochastisches Spiel; Evolutionäre Spieltheorie